Microbiome of HIV-infected people. (May 2017) - Dubourg, Grégory; Surenaud, Mathieu; Lévy, Yves; Hüe, Sophie; Raoult, Didier
Abstract: Consistent interactions between the gut microbiome and adaptive immunity recently led several research groups to evaluate modifications of human gut microbiota composition during HIV infection. Herein we propose to review the shifts reported in infected individuals, as their correlation to disease progression. Though the gut microbiota is consistently altered in HIV individuals, the literature reveals several discrepancies, such as changes in microbial diversity associated with HIV status, taxa modified in infected subjects or influence of ART on gut flora restoration. Similarly, mechanisms involved in interactions between gut bacteria and immunity are to date poorly elucidated, emphasizing the importance of understanding how microbes can promote HIV replication. Further research is needed to propose adjuvant therapeutics dedicated to controlling disease progression through gut microbiome restoration.